Nucleotide-Induced Conformational Dynamics in ABC Transporters from Structure-Based Coarse Grained Modeling - Flechsig, Holger (Frontiers in Physics, 2016)
ATP-binding cassette (ABC) transporters are integral membrane proteins which mediate the exchange of diverse substrates across membranes powered by ATP molecules. Our understanding of their activity is still hampered since the conformational dynamics underlying the operation of such proteins cannot yet be resolved in detailed molecular dynamics studies. Here a coarse grained model which allows to mimic binding of nucleotides and follow subsequent conformational motions of full-length transporter structures in computer simulations is proposed and implemented. To justify its explanatory quality, the model is first applied to the maltose transporter system for which multiple conformations are known and we find that the model predictions agree remarkably well with the experimental data. For the MalK subunit the switching from open to the closed dimer configuration upon ATP binding is reproduced and, moreover, for the full-length maltose transporter, progression from inward-facing to the outward-facing state is correctly obtained. For the heme transporter HmuUV, for which only the free structure could yet be determined, the model was then applied to predict nucleotide-induced conformational motions. Upon binding of ATP-mimicking ligands the structure changed from a conformation in which the nucleotide-binding domains formed an open shape, to a conformation in which they were found in tight contact, while, at the same time, a pronounced rotation of the transmembrane domains was observed. This finding is supported by normal mode analysis, and, comparison with structural data of the homologous vitamin B12 transporter BtuCD suggests that the observed rotation mechanism may contribute a common functional aspect for this class of ABC transporters. Although in HmuuV noticeable rearrangement of essential transmembrane helices was detected, there are no indications from our simulations that ATP binding alone may facilitate propagation of substrate molecules in this transporter. Possible explanations are discussed in the light of currently debated transport scenarios of ABC transporters.